Manslaughter in road traffic: Contradictory case law based on misapplied dogmatics - Durán Huaringa, Rubén (2023)
The deaths that run red the roads with blood are a problem that arose when men began to use motor vehicles as a sign of modernity. The legal implications derived from the reckless behavior of road users, such as drivers or pedestrians, have not been treated with the same attention as mens rea cases. In this context, the subject matter of this research is the observance of dogmatic scholar theories that have not been fully and specifically developed to cases of concurrent recklessness, which implies a reinterpretation of foreign scholar doctrine in order to make a de lege ferenda proposal.